SEKS SEBAGAI PROFESI: PERSPEKTIF PSIKOLOGI PEREMPUAN PSK - Kresna, Ida Ayu Agung Maha Chandri; Sudiana, Naomi Preity Paramita (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT Female sex work is a highly stigmatized social phenomenon, causing the psychological experiences of women involved to be frequently overlooked. This article aims to examine how female sex workers construct meanings of self-identity, sexuality, and survival strategies while navigating social and structural pressures. The study employs a literature review method by analyzing national and international scholarly publications from the past ten years through systematic stages of source identification, literature selection, data extraction, and thematic analysis. The findings indicate that women’s involvement in sex work is not solely driven by economic factors but also reflects personal agency in responding to limited life opportunities. Their self-identity is shaped through continuous negotiation between professional demands, personal values, and prevailing social norms, while stigma contributes to anxiety, identity conflict, and emotional burden. Nevertheless, female sex workers demonstrate resilience through community support, spirituality, and emotional boundary management. The digitalization of sex work offers greater autonomy and control, yet also introduces risks of emotional isolation and security vulnerabilities. Overall, this review emphasizes the importance of an empathetic, contextual, and non-stigmatizing women’s psychology approach in understanding the lived experiences of female sex workers. ABSTRAK Pekerjaan seks perempuan merupakan fenomena sosial yang sarat stigma, sehingga pengalaman psikologis perempuan yang terlibat di dalamnya kerap terabaikan. Artikel ini bertujuan mengkaji bagaimana perempuan pekerja seks memaknai identitas diri, seksualitas, serta strategi bertahan hidup dalam menghadapi tekanan sosial dan struktural. Penelitian ini menggunakan metode literature review dengan menelaah publikasi ilmiah nasional dan internasional sepuluh tahun terakhir melalui tahapan pencarian sumber, seleksi literatur, ekstraksi temuan, dan analisis tematik. Hasil kajian menunjukkan bahwa keterlibatan perempuan dalam pekerjaan seks tidak hanya dipengaruhi faktor ekonomi, tetapi juga mencerminkan bentuk agensi personal dalam menghadapi keterbatasan hidup. Identitas diri terbentuk melalui proses negosiasi antara tuntutan profesi, nilai personal, dan norma sosial, sementara stigma berkontribusi pada kecemasan, konflik identitas, dan beban emosional. Meski demikian, perempuan pekerja seks menunjukkan resiliensi melalui dukungan komunitas, spiritualitas, serta pengelolaan batasan emosional. Digitalisasi pekerjaan seks memberikan peluang otonomi yang lebih besar, namun juga menghadirkan risiko isolasi emosional dan kerentanan keamanan. Kajian ini menegaskan pentingnya pendekatan psikologi perempuan yang empatik dan non-stigmatis.